Optical Investigation of p-GaAs/i-GaN0.38yAs1-1.38ySby/n-GaAs Quantum Wells Emitters - I. Guizani; C. Bilel; Malak Alrowaili; A. Rebey (Journal of Nanotechnology)
We have studied the 1.55 μm optical properties of p-GaAs/i-GaN0.38yAs1-1.38ySby/n-GaAs quantum wells using a self-consistent calculation combined with the anticrossing model. We have found that the increase of injected carriers’ density induces the increase of optical gain and radiative current density. The rise of doping density causes a blue shift of the fundamental transition energy accompanied with significant increase of optical gain. The quantum-conﬁned Stark effect on radiative current density is also studied. The variation of radiative current as function of well width and Sb composition is also examined. In order to operate the emission wavelength at the optical fiber telecommunication domain, we have adjusted the well parameters of p-GaAs/i-GaN0.38yAs1-1.38ySby/n-GaAs.